Associations of serum concentrations of metal nutrients with postpartum anemia among pregnant Chinese women: A large retrospective cohort study - Chen, Geng-dong; Pang, Ting-ting; Li, Peng-sheng; Zhou, Zi-xing; Gou, Xiao-yan; Wang, Hai-yan; Lin, Dong-xin; Fan, Da-zhi; Li, Hong-li; Liu, Zheng-ping (Frontiers in Nutrition, 2023)
Background & Aims: The association between serum concentrations of metal nutrients in pregnancy and postpartum anemia has not been widely studied. This study aimed to determine this association in a large retrospective cohort study. Methods: We included 14,829 Chinese women with singleton pregnancies. Serum concentrations of metals before 28 weeks of gestation, the occurrence of postpartum anemia and other potential covariates were obtained from their laboratory or medical records. Cox regression and restricted cubic spline regression models were used to explore the relationship between serum concentrations of metal nutrients in pregnancy and postpartum anemia. Results: After adjustment for covariates, higher concentrations of iron (Fe), magnesium (Mg) and zinc (Zn) and lower concentrations of copper (Cu) were associated with a lower risk of postpartum anemia. Compared with those whose serum concentrations of metal nutrients were in the bottom quintile (Q1), the hazard ratios (HRs) of those whose serum concentrations of metal nutrients were in the top quintile (Q5) were 0.57 (95% confidence interval (CI): 0.50, 0.64) for Fe, 0.67 (95% CI: 0.60, 0.76) for Mg, 0.82 (95% CI: 0.73, 0.93) for Zn, and 1.44 (95% CI: 1.28, 1.63) for Cu. L-shaped curve relationships were found between increasing concentrations of Fe, Mg, and Zn and incidence of postpartum anemia. Higher serum concentrations of Cu were associated with an increased risk of postpartum anemia. Serum concentrations of Fe in Q5 were associated with a lower risk of postpartum anemia when they coincided with serum concentrations of Mg in Q5, Zn in Q5, or Cu in Q1. Conclusions: Higher serum concentrations of Fe, Mg, and Zn, and lower serum concentrations of Cu were associated with a lower risk of postpartum anemia among pregnant women.